A copper-coated powder metallurgy oil-impregnated bearing and a method for producing the same

CN122999989APending Publication Date: 2026-10-30CHANGZHOU GREAT POWDER METALLURGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611520152.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-29
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0007]本发明针对现有铁基粉末冶金含油轴承中,铜锡预合金粉虽能提高强度,但铜难以均匀覆盖连通孔道深部表面,常规电镀液无法进入细小孔道,烧结后镀铜易引起尺寸变化、难以兼顾多孔结构与自润滑性能的技术问题,提供一种铜包覆粉末冶金含油轴承及其制备方法,其在烧结精整后对烧结坯实施真空脉冲化学铜沉积,使铜沉积层形成于轴承外表面与连通孔道内壁,并在浸油前不再进行压制精整,从而在保持孔隙率的同时改善孔道表面润滑特性,提高自润滑性能与尺寸一致性

Benefits of technology

1.本发明将真空脉冲化学铜沉积设置在烧结和镀前尺寸精整完成之后、浸油之前,通过交替抽真空与恢复常压使化学镀铜液在压差驱动下反复进入并更新烧结坯的连通孔道,使铜沉积层同时形成于轴承外表面及内部连通孔道内壁,克服了常规电镀和常压化学镀难以使铜覆盖孔道深部、铜层集中于外表面的缺陷,提高了铜在多孔骨架表面分布的均匀性与覆盖完整性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999989A_ABST
    Figure CN122999989A_ABST
Patent Text Reader

Abstract

The application discloses a copper-coated powder metallurgy oil-impregnated bearing and a preparation method thereof, and belongs to the technical field of powder metallurgy oil-impregnated bearings. The method uses reduced iron powder as a main material, cooperates with copper-tin pre-alloy powder, flaky graphite powder and manganese sulfide powder, and obtains an iron-based porous sintered blank through mixing, pressing, degreasing, sintering and size finishing. After acid activation and copper deposition initiation treatment, the sintered blank is immersed in a chemical copper plating solution, vacuum pulse chemical copper deposition is alternately performed on the sintered blank by vacuumizing and restoring normal pressure, copper deposition layers are formed on the outer surface of the bearing and the inner wall of the communicating hole at the same time, and then the finished product is obtained through cleaning, reduction and vacuum oil immersion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of powder metallurgy oil-impregnated bearing technology, specifically to a copper-clad powder metallurgy oil-impregnated bearing and its preparation method. Background Technology

[0002] Powder metallurgy oil-impregnated bearings are produced by pressing and sintering metal powder into a porous structure, then impregnating it with lubricating oil to achieve self-lubrication. They can operate for extended periods without external oil supply or with only a small amount of added grease, and are widely used in applications requiring low-friction operation, such as motors in household appliances, power tools, office automation equipment, and automotive auxiliary components. Iron-based oil-impregnated bearings use iron as the main skeleton, combining high load-bearing capacity with moderate manufacturing costs. Their porosity, the degree of pore connectivity, and the properties of the inner surface of the pores directly determine the amount and retention capacity of lubricating oil, thus affecting the bearing's coefficient of friction, temperature rise, and service life.

[0003] Introducing copper into the iron-based matrix is ​​a common method to improve the strength of oil-impregnated bearings and their dry friction and boundary lubrication performance. Copper is usually added to the mixed powder in the form of electrolytic copper powder or copper-tin pre-alloyed powder, and partially forms a liquid phase during sintering to strengthen the metallurgical bond between the iron matrix components.

[0004] However, due to limitations in the diffusion between iron and copper and the liquid-phase sintering process window, the distribution of copper in the porous framework after sintering is difficult to uniformly cover the deep surface of the pores. The copper content is relatively high near the outer surface, while the copper distribution at the walls of the internal interconnected pores is limited. Methods to increase the copper content are often mutually constrained by the target porosity of the matrix, leading to a reduction in oil-bearing space or decreased pore connectivity, making it difficult to simultaneously achieve both oil-bearing capacity and surface tribological properties.

[0005] Some technologies attempt to improve the surface condition of iron-based oil-impregnated bearings through subsequent copper plating processes, i.e., depositing a copper layer on the outer surface of the sintered part. However, conventional electroplating makes it difficult for the plating solution to penetrate into the small internal interconnected channels, and the plating layer is mainly concentrated on the outer surface. If ordinary immersion chemical copper plating is used, the gas trapped inside the porous body and the surface tension of the plating solution will hinder the penetration of the plating solution into the depth of the channels, which can easily cause uneven deposition on the inner wall of the channels. The bonding and coverage of the copper layer with the substrate are still difficult to meet the long-term use requirements under harsh operating conditions.

[0006] Therefore, how to achieve uniform, stable, and well-bonded copper coverage on the surface of the sintered body and the walls of the internal interconnecting channels while maintaining the basic structure of the porous skeleton and oil-impregnated space of the bearing, and at the same time avoid adverse effects of subsequent processing on the final dimensions of the bearing, is a technical problem that needs to be solved in the manufacturing of iron-based powder metallurgy oil-impregnated bearings. Summary of the Invention

[0007] This invention addresses the technical problems in existing iron-based powder metallurgy oil-impregnated bearings. While copper-tin pre-alloyed powder can improve strength, copper is difficult to uniformly cover the deep surface of the interconnected channels. Conventional electroplating solutions cannot penetrate the fine channels, and copper plating after sintering easily causes dimensional changes, making it difficult to balance porous structure and self-lubricating performance. The invention provides a copper-coated powder metallurgy oil-impregnated bearing and its preparation method. After sintering and finishing, vacuum pulsed chemical copper deposition is performed on the sintered blank, so that a copper deposition layer is formed on the outer surface of the bearing and the inner wall of the interconnected channels. No pressing and finishing are performed before oil immersion, thereby improving the lubrication characteristics of the channel surface while maintaining porosity, and improving self-lubricating performance and dimensional consistency.

[0008] To achieve the above objectives, the technical solution adopted by the present invention is: a copper-clad powder metallurgy oil-impregnated bearing, the bearing comprising a sintered metal matrix and interconnecting channels distributed in the sintered metal matrix, the sintered metal matrix being obtained by pressing, degreasing, sintering, and finishing of mixed powders, the mixed powders comprising reduced iron powder, copper-tin pre-alloy powder, graphite powder, and manganese sulfide powder, wherein, based on 100 parts by weight of reduced iron powder, the copper-tin pre-alloy powder comprises 5.0–8.0 parts by weight, the graphite powder comprises 1.0–1.6 parts by weight, and the manganese sulfide powder comprises 0.4–0.8 parts by weight, and the total copper content of the bearing is 5.5–9.8 wt%, the porosity of the bearing is 14–22%, and the inner surface of the interconnecting channels and the outer surface of the sintered metal matrix both have a copper deposition layer, the copper deposition layer being formed by a vacuum pulsed chemical copper deposition process in a chemical copper plating solution, the mass of which is 1.5–3.5% of the mass of the sintered metal matrix.

[0009] Furthermore, the reduced iron powder has a D50 particle size of 45–90 μm, the copper-tin pre-alloyed powder has a D50 particle size of 20–45 μm, the graphite powder has a D50 particle size of 10–30 μm, and the manganese sulfide powder has a D50 particle size of 5–25 μm.

[0010] Furthermore, the copper-tin pre-alloyed powder is composed of 88-92 wt% copper and 8-12 wt% tin, the reduced iron powder has a median particle size of 45-60 μm, the graphite powder is flake graphite, and the manganese sulfide powder is in powder form.

[0011] A method for preparing a copper-coated powder metallurgy oil-impregnated bearing includes the following steps: S1: Mix reduced iron powder, copper-tin pre-alloyed powder, graphite powder and manganese sulfide powder evenly according to the above ratio to obtain a mixed powder; S2: The mixed powder is loaded into a bearing molding die and pressed into an annular preform under a pressure of 400–550 MPa, controlling the apparent density of the annular preform to be 5.9–6.3 g / cm³. 3 ; S3: The annular compact is heated to 380-450°C in a nitrogen atmosphere and held for 30-60 minutes for degreasing. Then, it is heated to 860-910°C in a hydrogen protective atmosphere and held for 25-45 minutes for sintering. After being cooled to below 150°C in the furnace, it is taken out of the furnace to obtain an iron-based porous sintered compact. S4: The iron-based porous sintered billet is dimensionally refined, and the inner and outer diameters of the bearing are reserved for dimensional compensation based on the subsequent copper deposition amount, so that the copper-clad bearing billet after the reduction treatment in step S6 reaches the target finished product size; the refined sintered billet is sequentially degreased and cleaned, acid activated and copper deposition initiated to obtain an activated sintered billet; S5: The activated sintered blank is completely immersed in the electroless copper plating solution. The processing container holding the activated sintered blank and the electroless copper plating solution is alternately vacuumed and restored to normal pressure at 55-70°C. This allows the electroless copper plating solution to enter the connecting channels of the activated sintered blank and cause electroless copper deposition. The mass increase rate of the sintered blank is controlled to be 1.5-3.5%, and a copper-deposited sintered blank is obtained. S6: The copper deposited sintered blank is subjected to deionized water vacuum pulse cleaning, then dried, and then subjected to reduction treatment at 300-380℃ for 30-60 min in a hydrogen-containing protective atmosphere to obtain copper-clad bearing blank. S7: Place the copper-clad bearing blank in lubricating oil, evacuate it at 70-90°C to an absolute pressure not exceeding 10 kPa and maintain it for 15-30 minutes, then restore it to normal pressure and maintain it for 20-40 minutes. Remove it and remove the surface oil to obtain a copper-clad powder metallurgy oil-impregnated bearing.

[0012] Furthermore, in step S5, the electroless copper plating solution contains copper sulfate pentahydrate, disodium ethylenediaminetetraacetate dihydrate, glyoxylic acid (calculated as pure glyoxylic acid), polyethylene glycol with an average molecular weight of 400-800, and 2,2'-bipyridine, and sodium hydroxide is used to adjust the pH of the electroless copper plating solution to 12.2-12.6.

[0013] Further, in step S5, after the activated sintered blank is completely immersed in the chemical copper plating solution, the absolute pressure of the treatment container is reduced to 40-60 kPa and maintained for 2-5 min, then restored to atmospheric pressure and maintained for 3-8 min. The vacuuming and atmospheric pressure restoration operation is repeated 3-6 times, and then chemical deposition is continued at atmospheric pressure and 55-70°C for 15-35 min.

[0014] Furthermore, in step S4, acid activation is performed using a hydrochloric acid aqueous solution with a mass concentration of 1.0–2.5%, treated at 20–35°C for 30–90 seconds. The initiation of copper deposition is performed by immersing the acid-activated sintered blank in an initiation solution containing copper sulfate pentahydrate and sodium citrate with a pH of 4.5–5.5 for 15–60 seconds.

[0015] Furthermore, in step S6, the deionized water vacuum pulse cleaning is performed at least twice. Each cleaning includes reducing the absolute pressure to 8-20 kPa and maintaining it for 2-5 minutes before restoring it to normal pressure, until the pH of the final cleaning solution is 6.5-7.5 and the conductivity is not higher than 100 μS / cm. Drying is carried out at 80-120°C and an absolute pressure not higher than 10 kPa, with a drying time of 60-120 minutes.

[0016] Furthermore, in step S7, the polyalphaolefin base oil of the lubricating oil used has a kinematic viscosity of 28–68 mmHg at 40°C. 2 / s.

[0017] A copper-clad powder metallurgy oil-impregnated bearing can be used in the manufacture of rolling bearings such as industrial robot bearings and high-speed train bearings.

[0018] A copper-clad powder metallurgy oil-impregnated bearing may also contain micron-sized semiconductor wafers.

[0019] In this invention, the pores of the iron-based porous sintered billet provide a through path for subsequent copper deposition. Vacuum pulse operation, through repeated depressurization and pressurization, removes stagnant gas within the pores and allows fresh plating solution to continuously penetrate deep into the pores. This allows a copper deposition layer to form simultaneously on the outer surface of the sintered metal substrate and the inner surface of the connecting pores, with the deposition amount controlled to 1.5–3.5% of the sintered billet mass, ensuring effective coverage without significantly reducing porosity. Copper deposition is performed after sintering and pre-plating dimensional finishing. Pre-plating finishing allows for dimensional compensation of the inner and outer diameters based on the expected copper deposition amount. No further pressing finishing is performed after copper deposition, thus avoiding secondary plastic deformation that could damage the formed copper layer and pore morphology. The reduction treatment is completed under low-temperature conditions in a hydrogen-containing atmosphere, which is beneficial for obtaining a copper layer with good bonding to the iron substrate and a clean surface, and provides a stable pore structure for further vacuum oil immersion. The finished product dimensions are determined by the pre-plating compensation amount and the controlled copper deposition amount. The above steps are interconnected, together forming a technical solution in which copper is uniformly covered on the surface of the sintered body and the walls of the internal channels, and has good dimensional stability.

[0020] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention sets up vacuum pulsed chemical copper deposition after sintering and pre-plating dimensional finishing, but before oil immersion. By alternating vacuuming and restoring atmospheric pressure, the chemical copper plating solution is repeatedly driven by pressure difference to enter and renew the connecting channels of the sintered blank. This allows the copper deposition layer to be formed simultaneously on the outer surface of the bearing and the inner wall of the internal connecting channels. This overcomes the defects of conventional electroplating and atmospheric pressure chemical plating, which make it difficult to cover the deep parts of the channels with copper and concentrate the copper layer on the outer surface. It improves the uniformity and integrity of the copper distribution on the porous skeleton surface.

[0021] 2. This invention introduces some copper through chemical deposition rather than by pressing with external copper powder. The copper deposit layer grows directly on the iron-based surface that has been acid-activated and treated to induce copper deposition. This is combined with low-temperature reduction treatment in a hydrogen-containing atmosphere, which ensures a good bond between the copper layer and the sintered metal matrix. At the same time, the amount of copper deposited is limited to a predetermined range, which ensures effective coverage of the inner wall and outer surface of the pores, while avoiding excessive growth of the copper layer that may block the pore openings or significantly encroach on the oil storage space. This maintains the connectivity and oil-bearing capacity of the porous framework.

[0022] 3. This invention eliminates the need for plastic deformation processing such as pressing or finishing after copper deposition, thus avoiding damage to the formed copper deposition layer and channel morphology during subsequent processing. During pre-plating finishing, the inner and outer diameter compensation is reserved based on the expected copper deposition amount, and the post-plating dimensional changes are controlled by limiting the copper deposition quality increase rate, so that the reduced copper-clad bearing blank reaches the target finished product size, thereby taking into account both the integrity of the copper layer and dimensional consistency, which is conducive to stable mass production.

[0023] 4. This invention uses copper-tin pre-alloy powder, flake graphite powder and manganese sulfide powder to form a matrix reinforcement and solid lubrication system, and then superimposes a copper deposition layer covering the inner wall and outer surface of the channel. This allows the bearing to obtain a low steady-state friction coefficient while maintaining sufficient radial crush strength. The oil-impregnated space, load-bearing capacity and tribological properties are coordinated with each other, which expands the application range of iron-based oil-impregnated bearings in the absence of external oil supply.

[0024] 5. The preparation process of this invention can be achieved with conventional powder metallurgy equipment and chemical plating equipment. The steps of degreasing, sintering, finishing, copper deposition pretreatment, vacuum pulse chemical copper deposition, post-plating cleaning and reduction, and vacuum oil immersion are clearly connected in sequence and have clear parameter windows. The process is stable and controllable, and has reasonable tolerance for changes in formulation dosage and pulse parameters, which is convenient for industrial implementation. Attached Figure Description

[0025] Figure 1 The X-ray diffraction pattern is shown in the X-ray diffraction pattern of the powder sample of the copper-coated powder metallurgy oil-impregnated bearing obtained in Example 1 of the present invention after degreasing treatment, and the X-ray diffraction pattern is shown in the X-ray diffraction pattern of the powder sample of the oil-impregnated bearing in the same state obtained in Comparative Example 12 without chemical copper deposition.

[0026] Figure 2 This is a backscattered electron micrograph of the radial cross section of the copper-clad powder metallurgy oil-impregnated bearing obtained in Example 1 of the present invention, and the corresponding surface distribution diagram of copper elements. Detailed Implementation

[0027] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are merely some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0028] Example 1:

[0029] This embodiment prepares a copper-clad powder metallurgy oil-impregnated bearing using the following raw materials: reduced iron powder with a D50 particle size of 55 μm, an oxygen content of 0.18 wt%, and a loose packing density of 2.75 g / cm³. 3 Copper-tin pre-alloyed powder, composed of 90wt% copper and 10wt% tin, with a D50 particle size of 35μm; flake graphite powder, with a D50 particle size of 20μm; manganese sulfide powder, with a D50 particle size of 12μm; ethylene bis-stearamide, as a molding lubricant.

[0030] S1: Ingredient Mixing: Based on 1000.0g of reduced iron powder, weigh out 1000.0g of reduced iron powder, 60.0g of copper-tin pre-alloyed powder, 13.0g of flake graphite powder, 6.0g of manganese sulfide powder, and 3.0g of ethylene bis-stearamide. Mix the above powders in a V-type mixer at a speed of 25 rpm for 60 minutes to obtain a mixed powder.

[0031] S2: Pressing: The mixed powder is pressed into ring-shaped preforms in an automatic powder forming machine. Each preform contains 12.02g of powder, with an outer diameter of 16.0mm, an inner diameter of 8.0mm, and a height of 12.8mm. The pressing pressure is set to 520MPa, the holding time is 1s, and the apparent density of the preform, calculated based on its mass and geometric volume, is 6.23g / cm³. 3 A total of 90 ring-shaped blanks were produced.

[0032] S3: Degreasing and Sintering: Ninety annular pressed billets were placed in a mesh belt sintering furnace. First, the furnace was purged with nitrogen at a flow rate of 1.5 m³ / h, and the temperature was increased from room temperature to 420°C at a rate of 8°C / min, held for 40 min for degreasing to allow the ethylene bis-stearamide to decompose and escape. Then, the atmosphere was switched to a hydrogen-containing protective atmosphere, consisting of 6% hydrogen and the remainder nitrogen, and the temperature was increased to 890°C at a rate of 5°C / min, held for 30 min for sintering. After sintering, the billets were cooled to 400°C under a hydrogen-containing protective atmosphere at a rate of 6°C / min, then switched back to a nitrogen atmosphere for further cooling, and finally removed from the furnace at below 120°C to obtain iron-based porous sintered billets. The average open porosity of the sintered billets, measured using the vacuum saturated weighing method, was 15.2%.

[0033] S4: Finishing and copper deposition pretreatment: The iron-based porous sintered billet is placed in a finishing mold and dimensionally finished with a pressure of 280MPa, and a compensation amount is reserved according to the influence of the subsequent copper deposition layer on the macroscopic dimensions; In this embodiment, the inner diameter before plating is 0.010mm larger than the inner diameter of the target finished product, and the outer diameter before plating is 0.010mm smaller than the outer diameter of the target finished product. After copper deposition and reduction, the inner and outer diameters of the finished product are checked to ensure that they meet the design dimensions. The finished sintered billet was immersed in a 3% sodium hydroxide and 2% sodium carbonate aqueous solution and ultrasonically cleaned at 60°C for 8 minutes. After removal, it was rinsed three times with deionized water. Then, it was immersed in a 2.0% hydrochloric acid aqueous solution at 25°C for 60 seconds for acid activation. After removal, it was rinsed with deionized water until neutral. Subsequently, the sintered billet was immersed in an initiating solution containing 0.8g of copper sulfate pentahydrate and 1.2g of sodium citrate per 100g of deionized water. The pH was adjusted to 5.0 with citric acid. It was immersed at 25°C for 30 seconds to form a copper initiation layer on the iron surface through a displacement reaction, thus obtaining an activated sintered billet.

[0034] S5: Vacuum Pulse Chemical Copper Deposition: The activated sintered blanks are completely immersed in the chemical copper plating solution. The chemical copper plating solution is prepared based on 2000g of deionized water and contains 18.0g of copper sulfate pentahydrate, 64.0g of disodium ethylenediaminetetraacetate dihydrate, 15.0g of glyoxylic acid (calculated as pure glyoxylic acid), 0.72g of polyethylene glycol with an average molecular weight of 600, and 0.060g of 2,2'-bipyridine. The pH is adjusted to 12.4 using sodium hydroxide. The volume of the prepared chemical copper plating solution is approximately 2146mL. The treatment container is a vacuum immersion tank. 90 activated sintered blanks are placed in the tank, and the above-mentioned chemical copper plating solution is added until the liquid level completely covers the sintered blanks. The initial ratio of the plating solution volume to the total mass of the iron-based porous sintered blanks is approximately 2.0L / kg. During the chemical copper deposition process, copper-complexing agent replenishment solution was added four times. Each time, 120 mL of deionized water containing 30.0 g of copper sulfate pentahydrate and 10.0 g of disodium ethylenediaminetetraacetate dihydrate was added to replenish the copper source and complexing agent. The amount of sodium hydroxide in the replenishment solution was not preset to be fixed. Instead, a 30% sodium hydroxide aqueous solution was added by metering pump according to online pH feedback to maintain the pH at 12.4 ± 0.1 during the deposition process.

[0035] The absolute pressure inside the processing container was reduced to 50 kPa and maintained for 3 minutes, then restored to atmospheric pressure and maintained for 5 minutes, constituting one vacuum pulse cycle. After each vacuum pulse cycle, 12.0 g of 50% glyoxylic acid aqueous solution (equivalent to 6.0 g of pure glyoxylic acid) was added, for a total of 4 additions. After completing all vacuum pulse cycles, the plating bath temperature was maintained at 60°C, and chemical deposition continued for 25 minutes under atmospheric pressure. After deposition, the sintered blank was removed, thoroughly rinsed with deionized water, and subsequently reduced and dried in step S6 before verification. The net mass increase of the sintered blank compared to the pre-deposition dried sintered blank was 2.6%. Based on the estimated actual material input of 90 sintered blanks, minus the forming lubricant, approximately 1078.8g, the net weight gain is approximately 28.0g, which can be approximated as approximately 28.0g of actual deposited metal Cu, i.e., 0.441mol, corresponding to an actual consumption of approximately 110.2g of copper sulfate pentahydrate. The total input of initial and supplementary copper sulfate pentahydrate is 138.0g, with a copper source utilization rate of approximately 79.9%. The remaining approximately 20.1% corresponds to the residual Cu at the end of deposition. 2+ Workpiece carry-out and process losses are not assumed, and 100% conversion of copper source is not assumed. Based on the reduction of 1 mol of Cu by 1 mol of glyoxylic acid, the theoretical amount of glyoxylic acid reacted is about 32.7 g, and the actual total amount of pure glyoxylic acid added is 39.0 g, which is about 1.19 times the theoretical amount. During the reaction, a total of about 230-245 g of 30% sodium hydroxide aqueous solution was added, with the online pH as the final control basis.

[0036] S6: Post-plating treatment: The copper-deposited sintered billet was placed in a vacuum cleaning tank, completely submerged in deionized water, and the absolute pressure inside the tank was reduced to 12 kPa and maintained for 3 minutes. The pressure was then restored to normal, and this process was repeated three times. After each cleaning, the cleaning solution was poured out and replaced with fresh deionized water. The final cleaning solution had a pH of 7.0 and a conductivity of 15 μS / cm. The sintered billet was then vacuum-dried at 100°C and an absolute pressure of 5 kPa for 90 minutes. It was then placed in a hydrogen-containing protective atmosphere (6% hydrogen by volume and the remainder nitrogen) and held at 350°C for 45 minutes for reduction treatment to obtain the copper-clad bearing billet.

[0037] S7: Oil Immersion: The copper-clad bearing blank is completely immersed in lubricating oil. The lubricating oil contains 15.0g of trimellitic acid triester, 0.5g of alkyl diphenylamine, and 0.06g of benzotriazole per 100g of polyalphaolefin base oil. The kinematic viscosity of the polyalphaolefin base oil at 40℃ is 46mm. 2 / s. Before immersion in oil, the lubricating oil is degassed at 80℃ and 5kPa absolute pressure for 30 minutes. The copper-clad bearing blank is placed in the degassed lubricating oil, and a vacuum is drawn to 5kPa absolute pressure at 80℃ and maintained for 25 minutes. While keeping the bearing blank completely immersed in the lubricating oil, the pressure is restored to normal and maintained for 30 minutes. After removal, the surface oil is removed by centrifugation to obtain the copper-clad powder metallurgy oil-impregnated bearing.

[0038] In Figure 1, the main diffraction peaks around 44°, 65.0°, and 82° can be attributed to α-Fe, while those around 43°, 50°, and 74° correspond to the characteristic diffraction peaks of metallic Cu. The peak around 26° corresponds to the graphite in the formulation. The presence of adjacent double peaks in the 43°–45° region is reasonable due to the proximity of the Cu(111) and α-Fe(110) peaks. In Example 1, the characteristic Cu peaks around 50.4° and 74.1° are significantly enhanced relative to the Fe reference peaks. Although Comparative Example 12 did not undergo subsequent chemical copper deposition, its original formulation still contained copper-tin pre-alloyed powder, so the presence of Cu diffraction peaks of a certain intensity is correct and should not have completely disappeared. This trend is also consistent with the results in Table 1, where the total copper content of Example 1 is 7.4 wt% and that of Comparative Example 12 is 5.1 wt%.

[0039] In Figure 2, the porous iron-based sintered skeleton is mainly represented by gray areas in the BSE image, while the pores are represented by dark areas. Brighter high atomic number enriched areas appear on the outer surface of the bearing and at the edges of some pores. Correspondingly, the Cu element distribution map shows a continuous high-intensity Cu signal band on the outer surface, while obvious Cu signals appear in the contours of a large number of pores and on the pore walls inside. These Cu enriched areas basically correspond to the pore edges in the BSE image, which is consistent with the process mechanism of depressurizing and venting the gas in the pores during the vacuum pulse process, and then allowing the plating solution to further enter the pores and deposit copper on the pore walls after restoring normal pressure.

[0040] Example 2:

[0041] The difference between this embodiment and Embodiment 1 is that the pressing pressure and compact density, degreasing and sintering process parameters, and copper deposition amount are slightly different.

[0042] S1: Ingredient mixing: Based on 1000.0g of reduced iron powder, weigh out 1000.0g of reduced iron powder, 50.0g of copper-tin pre-alloyed powder, 10.0g of flake graphite powder, 4.0g of manganese sulfide powder, and 2.0g of ethylene bis-stearamide. The mixing method is the same as in Example 1, and the mixing time is 60min to obtain mixed powder.

[0043] S2: Pressing: The mixed powder is pressed into a ring-shaped compact. The outer and inner diameters of the compact are the same as in Example 1. The compact height is 13.5 mm, the powder content per piece is 12.02 g, the pressing pressure is set to 400 MPa, and the apparent density of the compact is 5.90 g / cm³. 3 88 ring-shaped blanks were actually produced, with 8.2g of mixed powder remaining.

[0044] S3: Degreasing and sintering: Degreasing was carried out at 380°C for 60 minutes in a nitrogen atmosphere; sintering was carried out at 860°C for 40 minutes in a hydrogen-containing protective atmosphere, which consisted of 5% hydrogen by volume and the remainder nitrogen. The remaining operations were the same as in Example 1. After being taken out of the furnace, an iron-based porous sintered billet was obtained with an open porosity of 19.8%.

[0045] S4: Finishing and copper deposition pretreatment: The finishing pressure is 200MPa, and the degreasing cleaning, acid activation and initiation solution treatment are the same as in Example 1. The acid activation time is 90s.

[0046] S5: Vacuum Pulse Chemical Copper Deposition: The activated sintered blank was completely immersed in the chemical copper plating solution, which used the same initial formulation as in Example 1, with an initial volume of approximately 2146 mL. The ratio of the initial plating solution volume to the total mass of the iron-based porous sintered blank was approximately 2.0 L / kg. The vacuum pulse cycle was performed 6 times. During each cycle, the absolute vacuum pressure was 60 kPa and maintained for 2 minutes, followed by a return to atmospheric pressure and a 3-minute maintenance. A copper-complexing agent replenishment solution was added between every two adjacent vacuum pulse cycles, for a total of 5 times. Each replenishment consisted of 60 mL of a deionized aqueous solution containing 15.0 g copper sulfate pentahydrate and 5.0 g disodium ethylenediaminetetraacetate dihydrate, along with 4.6 g of a 50% glyoxylic acid aqueous solution. During deposition, a 30% sodium hydroxide aqueous solution was added based on online pH feedback to maintain the pH at 12.4 ± 0.1. After completing the vacuum pulse cycle, deposition continued for 35 minutes at atmospheric pressure and 60°C. After reduction and drying in step S6, the net mass increase rate was verified to be 1.8%, corresponding to an actual deposited Cu of approximately 19.0 g and an actual consumption of approximately 74.7 g of copper sulfate pentahydrate. The total input of copper sulfate pentahydrate was 93.0 g, and the copper source utilization rate was approximately 80.3%. The theoretical glyoxylic acid reaction amount was approximately 22.1 g, and the actual total added pure glyoxylic acid was approximately 26.5 g, which is approximately 1.20 times the theoretical amount.

[0047] S6~S7: Post-plating treatment and oil immersion operation are the same as in Example 1, and the reduction treatment is held at 300℃ for 60 minutes.

[0048] Example 3:

[0049] S1: Ingredient mixing: Based on 1000.0g of reduced iron powder, weigh out 1000.0g of reduced iron powder, 70.0g of copper-tin pre-alloyed powder, 14.0g of flake graphite powder, 7.0g of manganese sulfide powder, and 3.5g of ethylene bis-stearamide. The mixing method is the same as in Example 1 to obtain mixed powder.

[0050] S2: Pressing: The outer and inner diameters of the pressed billet are the same as in Example 1, and the height of the pressed billet is 13.07 mm; the pressing pressure is set to 480 MPa, and the apparent density of the pressed billet is 6.10 g / cm³. 3 Each piece contained 12.02g of powder, and 91 pressed blanks were actually produced.

[0051] S3: Degreasing and sintering: Degreasing is carried out at 450°C for 30 minutes in a nitrogen atmosphere; sintering is carried out at 910°C for 25 minutes in a hydrogen-containing protective atmosphere, which consists of 8% hydrogen by volume and the remainder nitrogen. The remaining operations are the same as in Example 1. After exiting the furnace, an iron-based porous sintered billet is obtained with an open porosity of 16.5%.

[0052] S4: Finishing and copper deposition pretreatment: Finishing pressure is 300MPa, acid activation time is 30s, and the rest is the same as in Example 1.

[0053] S5: Vacuum Pulse Chemical Copper Deposition: The chemical copper plating solution used the same initial formulation as in Example 1, with an initial volume of approximately 2146 mL. The ratio of the initial plating solution volume to the total mass of the iron-based porous sintered billet was approximately 2.0 L / kg. The vacuum pulse cycle was performed three times. In each cycle, the absolute vacuum pressure was 40 kPa and maintained for 5 minutes, followed by 8 minutes after returning to normal pressure. A copper-complexing agent replenishment solution was added twice between every two adjacent vacuum pulse cycles. Each time, 250 mL of a deionized aqueous solution containing 77.0 g copper sulfate pentahydrate and 26.0 g disodium ethylenediaminetetraacetate dihydrate was added, along with 34.0 g of a 50% glyoxylic acid aqueous solution. A 30% sodium hydroxide aqueous solution was added based on online pH feedback to maintain the pH at 12.4 ± 0.1. After completing three vacuum pulse cycles, deposition continued for 15 minutes at 60°C and normal pressure. After reduction and drying in step S6, the net mass increase rate was verified to be 3.2%, corresponding to an actual deposited Cu of approximately 34.9 g and an actual consumption of approximately 137.1 g of copper sulfate pentahydrate. The total input of copper sulfate pentahydrate was 172.0 g, and the copper source utilization rate was approximately 79.7%. The theoretical glyoxylic acid reaction amount was approximately 40.7 g, and the actual total added pure glyoxylic acid was approximately 49.0 g, which is approximately 1.20 times the theoretical amount.

[0054] S6~S7: Post-plating treatment and oil immersion operation are the same as in Example 1, and the reduction treatment is held at 380℃ for 30 minutes.

[0055] Example 4:

[0056] S1: Ingredient mixing: Based on 1000.0g of reduced iron powder, weigh out 1000.0g of reduced iron powder, 80.0g of copper-tin pre-alloyed powder, 16.0g of flake graphite powder, 8.0g of manganese sulfide powder, and 4.0g of ethylene bis-stearamide. The mixing method is the same as in Example 1 to obtain mixed powder.

[0057] S2: Pressing: The outer and inner diameters of the pressed billet are the same as in Example 1, and the height of the pressed billet is 13.18 mm; the pressing pressure is set to 460 MPa, and the apparent density of the pressed billet is 6.05 g / cm³. 3 Each piece contained 12.02g of powder, and 92 pressed blanks were actually produced.

[0058] S3: Degreasing and sintering: Degreasing was carried out at 420°C for 40 minutes in a nitrogen atmosphere; sintering was carried out at 890°C for 30 minutes in a hydrogen-containing protective atmosphere, which consisted of 7% hydrogen by volume and the remainder nitrogen. The remaining operations were the same as in Example 1. After being taken out of the furnace, an iron-based porous sintered billet was obtained with an open porosity of 14.2%.

[0059] S4: Finishing and copper deposition pretreatment: The finishing pressure is 250 MPa, and the remaining operations are the same as in Example 1.

[0060] S5: Vacuum Pulse Chemical Copper Deposition: The chemical copper plating solution used the same initial formulation as in Example 1, with an initial volume of approximately 2146 mL. The ratio of the initial plating solution volume to the total mass of the iron-based porous sintered billet was approximately 2.0 L / kg. The vacuum pulse cycle was performed 5 times. In each cycle, the absolute vacuum pressure was 45 kPa and maintained for 4 min, followed by a return to atmospheric pressure and a maintenance period of 6 min. A copper-complexing agent replenishment solution was added between every two adjacent vacuum pulse cycles, for a total of 4 times. Each replenishment consisted of 120 mL of a deionized aqueous solution containing 25.5 g of copper sulfate pentahydrate and 8.5 g of disodium ethylenediaminetetraacetate dihydrate, along with 9.5 g of a 50% glyoxylic acid aqueous solution. A 30% sodium hydroxide aqueous solution was added based on online pH feedback to maintain the pH at 12.4 ± 0.1. After completing 5 vacuum pulse cycles, deposition continued for 20 min at 60°C and atmospheric pressure. After reduction and drying in step S6, the net mass increase rate was verified to be 2.2%, corresponding to an actual deposited Cu of approximately 24.2g and an actual consumption of approximately 95.2g of copper sulfate pentahydrate. The total input of copper sulfate pentahydrate was 120.0g, and the copper source utilization rate was approximately 79.4%. The theoretical glyoxylic acid reaction amount was approximately 28.2g, and the actual total added pure glyoxylic acid was approximately 34.0g, which is approximately 1.20 times the theoretical amount.

[0061] S6~S7: Post-plating treatment and oil immersion operation are the same as in Example 1.

[0062] Example 5:

[0063] S1: Ingredient mixing: Based on 1000.0g of reduced iron powder, weigh out 1000.0g of reduced iron powder, 55.0g of copper-tin pre-alloyed powder, 11.0g of flake graphite powder, 5.0g of manganese sulfide powder, and 2.8g of ethylene bis-stearamide. The mixing method is the same as in Example 1 to obtain mixed powder.

[0064] S2: Pressing: The outer and inner diameters of the pressed billet are the same as in Example 1, and the height of the pressed billet is 12.75 mm; the pressing pressure is set to 550 MPa, and the apparent density of the pressed billet is 6.25 g / cm³. 3 Each piece contained 12.02g of powder, and 89 pressed blanks were actually produced.

[0065] S3: Degreasing and sintering: Degreasing was carried out at 420°C for 40 minutes in a nitrogen atmosphere; sintering was carried out at 880°C for 35 minutes in a hydrogen-containing protective atmosphere, which consisted of 4% hydrogen by volume and the remainder nitrogen. The remaining operations were the same as in Example 1. After being taken out of the furnace, an iron-based porous sintered billet was obtained with an open porosity of 15.2%.

[0066] S4: Finishing and copper deposition pretreatment: The finishing pressure is 320 MPa, and the remaining operations are the same as in Example 1.

[0067] S5: Vacuum Pulse Chemical Copper Deposition: The chemical copper plating solution used the same initial formulation as in Example 1, with an initial volume of approximately 2146 mL. The ratio of the initial plating solution volume to the total mass of the iron-based porous sintered billet was approximately 2.0 L / kg. The vacuum pulse cycle was performed three times. During each cycle, the absolute vacuum pressure was 45 kPa and maintained for 5 minutes, followed by a return to atmospheric pressure and a 5-minute maintenance period. A copper-complexing agent replenishment solution was added twice between every two adjacent vacuum pulse cycles. Each time, 220 mL of a deionized aqueous solution containing 70.0 g copper sulfate pentahydrate and 24.0 g disodium ethylenediaminetetraacetate dihydrate was added, along with 30.0 g of a 50% glyoxylic acid aqueous solution. A 30% sodium hydroxide aqueous solution was added based on online pH feedback to maintain the pH at 12.4 ± 0.1. After completing three vacuum pulse cycles, deposition continued for 30 minutes at 60°C and atmospheric pressure. After reduction and drying in step S6, the net mass increase rate was verified to be 3.0%, corresponding to an actual deposited Cu of approximately 32.0 g and an actual consumption of approximately 125.8 g of copper sulfate pentahydrate. The total input of copper sulfate pentahydrate was 158.0 g, and the copper source utilization rate was approximately 79.6%. The theoretical glyoxylic acid reaction amount was approximately 37.3 g, and the actual total added pure glyoxylic acid was approximately 45.0 g, which is approximately 1.21 times the theoretical amount.

[0068] S6~S7: Post-plating treatment and oil immersion operation are the same as in Example 1.

[0069] Comparative Example 1: The preparation of a copper-clad powder metallurgy oil-impregnated bearing follows the preparation method of Example 1, except that the pressing pressure is replaced with 350 MPa instead of 520 MPa, while the rest remains the same as in Example 1. Following the powder loading method of Example 1, 12.02 g / piece is loaded into the mold cavity, and 10 pieces are pressed into shape. The apparent density of the pressed blank is 5.38 g / cm³. 3 The blank is intact, without any forming defects such as delamination or cracking.

[0070] Comparative Example 2: A copper-clad powder metallurgy oil-impregnated bearing was prepared by referring to the preparation method of Example 1, except that the pressing pressure was replaced with 600 MPa instead of 520 MPa, while the rest remained the same as in Example 1. Following the powder loading method of Example 1, 12.02 g / piece was loaded into the mold cavity, and 10 pieces were pressed into shape. The apparent density of the pressed blank was 6.44 g / cm³. 3 The blank is intact, without any forming defects such as delamination or cracking.

[0071] Comparative Example 3: The preparation of a copper-clad powder metallurgy oil-impregnated bearing follows the preparation method of Example 1, except that the amount of copper-tin pre-alloyed powder is replaced from 60.0g to 40.0g, which is 4.0 parts by mass relative to 100 parts by mass of reduced iron powder. The rest remains the same as in Example 1. In this comparative example, the mixed powder is based on 1000.0g of reduced iron powder. During pressing, the powder loading is 12.02g / piece as in Example 1, and a total of 10 pieces are pressed. The apparent density of the pressed blank is 6.08g / cm³. 3 The blank is intact.

[0072] Comparative Example 4: A copper-clad powder metallurgy oil-impregnated bearing was prepared according to the preparation method of Example 1, except that the amount of flake graphite powder was replaced from 13.0g to 20.0g, which is 2.0 parts by mass relative to 100 parts by mass of reduced iron powder. The rest remained the same as in Example 1. In this comparative example, the mixed powder was based on 1000.0g of reduced iron powder. During pressing, the powder loading was 12.02g / piece as in Example 1, and a total of 10 pieces were pressed. The apparent density of the pressed blank was 5.92g / cm³. 3 The blank is intact and has no cracks on the surface, but a small amount of powder falls off the edges when demolding. After cleaning, it can be used for subsequent processes.

[0073] Comparative Example 5: The preparation of a copper-clad powder metallurgy oil-impregnated bearing follows the preparation method of Example 1, except that the amount of manganese sulfide powder is replaced from 6.0g to 2.0g, which is 0.2 parts by mass relative to 100 parts by mass of reduced iron powder. The rest remains the same as in Example 1. In this comparative example, the mixed powder is based on 1000.0g of reduced iron powder. During pressing, the powder loading is 12.02g / piece as in Example 1, and a total of 10 pieces are pressed. The apparent density of the pressed blank is 6.15g / cm³. 3 The blank is intact.

[0074] Comparative Example 6: The preparation of a copper-clad powder metallurgy oil-impregnated bearing followed the preparation method of Example 1, except that the degreasing temperature was changed from 420℃ to 340℃, while the rest remained the same as in Example 1. After degreasing at 340℃ for 40 minutes, the total mass loss of 90 blanks was approximately 1.1g, accounting for about 0.10% of the total powder mass, which was significantly lower than the approximately 3.0g that should have been removed according to the actual amount of ethylene bis-stearamide added, indicating that the forming lubricant was not fully removed. Subsequently, during sintering in a hydrogen-containing protective atmosphere at 890℃, the residual organic matter continued to decompose and form a small amount of carbon residue, which adversely affected the neck bonding of the sintered particles and subsequent surface activation. The porosity of the resulting sintered blank was 16.2%. After further finishing, copper deposition, and oil impregnation according to Example 1, the final net mass increase of copper deposition was 1.2%.

[0075] Comparative Example 7: The preparation of a copper-clad powder metallurgy oil-impregnated bearing follows the preparation method of Example 1, except that the sintering temperature is changed from 890℃ to 940℃, while the rest remains the same as in Example 1. After sintering at 940℃, the porosity of the sintered blank is 9.5%, and although there are no cracks on the surface, local erosion pits appear, indicating that the excessively high sintering temperature causes significant shrinkage of the pores and reduces their connectivity. The finishing, acid activation, vacuum pulsed chemical copper deposition, and oil immersion are then carried out according to Example 1. Because copper deposition can still occur on the outer surface while the effective internal interconnected pores are reduced, the final net increase in copper deposition mass is 1.1%, lower than in Example 1, but not without copper deposition.

[0076] Comparative Example 8: The preparation of a copper-clad powder metallurgy oil-impregnated bearing was carried out according to the preparation method of Example 1, except that the holding time after restoring normal pressure was replaced from 5 min to 2 min, while the rest remained the same as in Example 1. The powder loading method and process route of Example 1 were followed. Pressing, degreasing and sintering, finishing, acid activation, and initiation treatment were all the same as in Example 1. The composition and replenishment method of the electroless copper plating solution were also the same as in Example 1. After completing four vacuum pulse cycles, chemical deposition was continued for 25 min at 60°C and normal pressure. The measured mass increase rate of the sintered blank was 2.1%, lower than the 2.6% of Example 1.

[0077] Comparative Example 9: The preparation of a copper-clad powder metallurgy oil-impregnated bearing follows the preparation method of Example 1, except that the absolute vacuum pressure is replaced from 50 kPa to 15 kPa, while the rest remains the same as in Example 1. Under the conditions of a plating bath temperature of 60°C and an absolute vacuum pressure of 15 kPa, the plating bath exhibits significant boiling and generates a large number of bubbles, accompanied by a small amount of plating bath splashing, making the deposition process unstable. The actual measured increase in copper deposition mass is 0.2%, significantly lower than in Example 1, indicating that the absolute pressure is below the lower limit of stable operation of the electroless copper plating solution at this temperature.

[0078] Comparative Example 10: The preparation of a copper-coated powder metallurgy oil-impregnated bearing follows the preparation method of Example 1, except that the pH of the electroless copper plating solution is changed from 12.4 to 12.0, while the rest remains the same as in Example 1. Under the condition of a plating solution pH of 12.0, the plating solution remains essentially clear, but the reduction rate of glyoxylic acid decreases, the deposition induction period is prolonged, and the copper deposition rate per unit time is significantly reduced. The actual measured net increase in copper deposition mass is 0.5%, significantly lower than in Example 1, indicating that this pH is below the suitable range for obtaining a stable deposition rate in this system.

[0079] Comparative Example 11: The preparation of a copper-clad powder metallurgy oil-impregnated bearing follows the preparation method of Example 1, except that the acid activation and copper deposition initiation treatment in step S4 are replaced with palladium activation using a palladium chloride activation solution. The activation solution is an aqueous solution of 0.5 g / L palladium chloride and 5 mL / L hydrochloric acid. The bearing is immersed at 25°C for 15 min, washed with deionized water, and then directly subjected to the electroless copper plating in step S5. However, step S5 does not involve vacuuming and restoring atmospheric pressure via vacuum pulse cycling; instead, the sintered blank is immersed in the electroless copper plating solution at 60°C and atmospheric pressure for continuous deposition for 120 min. The remaining steps are the same as in Example 1. This comparative example uses the same electroless copper plating solution composition and replenishment method as Example 1, but due to the lack of pressure differential drive, copper deposition mainly occurs on the outer surface of the sintered blank, with a thinner deposition layer on the inner wall of the connecting channels.

[0080] Comparative Example 12: The preparation of a copper-clad powder metallurgy oil-impregnated bearing, referring to Example 1, involves directly vacuum immersing the degreased and sintered iron-based porous sintered blank without finishing, acid activation, and vacuum pulsed chemical copper deposition treatment. That is, the blank is first immersed in the same lubricating oil as in Example 1, and kept at a temperature of 80°C and an absolute pressure of 5 kPa for 30 min, then restored to normal pressure and kept for 30 min, and then removed to remove the surface oil.

[0081] Comparative Example 13: The preparation of a copper-clad powder metallurgy oil-impregnated bearing, referring to Example 1, involves replacing step S5 with the following: The sintered blank treated in step S4 is first placed in a sealed container, and steam is introduced at an absolute pressure of 10 kPa for 10 minutes to replace the gas in the pores. Then, atmospheric pressure is restored, and a chemical copper plating solution is injected to completely immerse the sintered blank. The blank is then immersed in the solution at 60°C and atmospheric pressure for 120 minutes without vacuum pulses. Subsequent deionized water cleaning, drying, and reduction treatments are the same as in Example 1. In this comparative example, steam replacement only removes some of the gas, and the chemical copper plating solution cannot uniformly fill the entire interconnected pore system, resulting in less copper deposition in the deeper parts of the pores.

[0082] Comparative Example 14: The preparation of a copper-clad powder metallurgy oil-impregnated bearing, referring to Example 1, involves replacing step S5 with a single vacuum immersion electroless plating: the sintered blank treated in step S4 is first completely immersed in the same electroless copper plating solution as in Example 1. The absolute pressure of the container is reduced to 50 kPa at 60°C and maintained for 10 min. Subsequently, atmospheric pressure is restored only once, and atmospheric pressure electroless deposition continues for 110 min, without any further vacuuming. The principles for replenishing the copper source, glyoxylic acid, and sodium hydroxide are the same as in Example 1. Subsequent deionized water rinsing, drying, and reduction treatments are the same as in Example 1. Although this comparative example allows some plating solution to enter the channels through a single pressure difference, it cannot repeatedly vent and refresh the plating solution within the channels during the deposition process. The copper deposition is still mainly concentrated on the outer surface and near-surface channels, and the measured net mass increase rate is 0.8%, lower than that of Example 1.

[0083] Performance testing methods: 1. Determination of open porosity: The test subjects were copper-clad bearing blanks prepared in the same batch as the target finished product, which had undergone steps S1 to S6, but had not yet undergone step S7 lubricating oil impregnation. The number of samples was 3.

[0084] Sample pretreatment: Immerse the sample in anhydrous ethanol and ultrasonically clean for 5 min. After removing it, dry it in an 80℃ hot air drying oven for 120 min, and then place it in a desiccator to cool to room temperature.

[0085] The test was conducted according to the mass-volume determination principle of GB / T5163-2006 "Determination of density, oil content and open porosity of permeable sintered metal materials (excluding cemented carbide)". The open porosity was determined using the vacuum saturated water weighing method. Considering that the sample was an iron-based porous material, to avoid weighing errors caused by oxidation or corrosion due to prolonged boiling water treatment, room temperature vacuum degassing and restoration to normal pressure were used to ensure that deionized water fully entered the interconnected channels.

[0086] The test procedure is as follows: First, weigh the mass m0 of the dried sample in air; then, completely immerse the sample in pre-degassed deionized water, reduce the absolute pressure of the container to below 5 kPa at 23℃±2℃ and maintain this pressure for 30 minutes. Next, while keeping the sample submerged, restore the pressure to atmospheric pressure and maintain this pressure for 30 minutes. Repeat this vacuum-atmospheric pressure process once to ensure the open pores are fully saturated with water. Then, suspend the saturated sample in deionized water at the same temperature and weigh the mass m1 in the water. Next, remove the sample and gently touch the surface with a pre-wetted, non-drip lint-free wiping material to remove the free water film on the outer surface. Immediately afterward, weigh the saturated mass m2 in air. The open porosity is determined using the following formula, and the result is expressed as the arithmetic mean of the measured values ​​of three samples: General calculation formula:

[0087] In the formula, θ is the porosity (%), m0 is the mass of the dry sample (g), m1 is the suspended mass of the saturated sample in water (g), and m2 is the mass of the saturated sample in air (g).

[0088] 2. Determination of volumetric oil content: The test subject was the final product, copper-clad powder metallurgy oil-impregnated bearing. Three samples were taken from each batch. First, the outer diameter D, inner diameter d, and height h of each sample were measured using an outside micrometer and an inside micrometer. The apparent volume of the bearing was calculated using the annular volume formula. Then, fiber-free oil-absorbing paper was applied to the outer surface and end face of the sample with consistent light pressure until no visible free oil film was visible. Petroleum ether or other organic solvents that can dissolve lubricating oil were not used before the first weighing to avoid extracting the effective oil content in the near-surface channels. The mass m1 of the oil-impregnated sample was weighed at 23℃±2℃. After weighing m1, the sample was placed in a Soxhlet extractor and extracted by heating and reflux for 8 hours using petroleum ether (boiling range 60~90℃) as the extraction solvent to fully extract the lubricating oil in the sample channels. The sample was then removed and dried in a 100℃ drying oven for 120 minutes, and then placed in a desiccator to cool to room temperature before weighing the mass m2 of the deoiled sample.

[0089] The density ρoil of the lubricating oil used was measured at 23°C using a densitometer, and the oil content was calculated according to GB / T5163-2006 "Determination of Density, Oil Content and Porosity of Sintered Metallic Materials (excluding cemented carbide) - Permeable Sintered Metallic Materials". This standard is applicable to the determination of density and oil content of porous sintered metal materials and oil-impregnated bearings. The porous interconnected structure of the copper-clad powder metallurgy oil-impregnated bearing sample of this invention is consistent with the applicable scope of the standard. The volumetric oil content was determined by the following formula: General calculation formula:

[0090] In the formula, φoil is the volumetric oil content (%), m1 is the mass of the oil-containing sample (g), m2 is the mass of the sample after degreasing (g), and ρoil is the density of the lubricating oil at 23℃ (g / cm³). 3 V represents the external volume of the bearing sample, in cm³. 3 According to the formula for the volume of a toroid, V = π(D / 2). 2 h-π(d / 2) 2 h was determined. The results are expressed as the arithmetic mean of the measured values ​​of the three extracted samples.

[0091] 3. Radial crushing strength determination: The test object was the final product, a copper-clad powder metallurgy oil-impregnated bearing, and three samples prepared under the same working conditions were used. The test method adopted the radial crush strength test method specified in the current national standard GB / T6804-2008 "Determination of Radial Crushing Strength of Sintered Metal Bushings". This standard is applicable to the radial crush strength determination of sintered metal bushings and ring bearings. The sample in this invention was a ring bearing with an outer diameter of 16.0 mm and an inner diameter of 8.0 mm, and its edge shape and loading method met the test requirements of this standard. The test was conducted on an electronic universal testing machine. The sample was placed sideways on the lower pressure plate, with the sample axis parallel to both the upper and lower pressure plates. The upper pressure head was kept parallel to the lower pressure plate, and the loading direction was perpendicular to the sample axis. The testing machine was calibrated to Class 1 accuracy.

[0092] The indenter speed is 2 mm / min, and loading is applied continuously until visible crush cracks appear on the specimen or the load reaches its peak and then decreases. The maximum crush load F is recorded. The radial crush strength is determined by the following formula: General calculation formula:

[0093] In the formula, K is the radial crushing strength in MPa; F is the maximum crushing load in N; D is the outer diameter of the specimen in mm; T is the single-sided wall thickness of the specimen in mm, T=(Dd) / 2, d is the inner diameter of the specimen in mm; and L is the height of the specimen in mm. The result is expressed as the arithmetic mean of the measured values ​​of three specimens.

[0094] 4. Determination of total copper content: This test is used to determine the proportion of the total mass of copper in a bearing to the total mass of the bearing metal and solid lubricant components. The value includes copper introduced from the copper-tin pre-alloy powder in the mixed powder and copper introduced from the vacuum pulsed chemical copper deposition step. This is used to verify whether the total copper content in the bearing is within the design range. This determination uses the acid digestion-inductively coupled plasma atomic emission spectrometry method according to JB / T14979-2025 "Determination of Copper Content in Iron-Based Powder Metallurgy Products - Inductively Coupled Plasma Atomic Emission Spectrometry". Considering that the formulation of this invention contains flake graphite, a small amount of insoluble carbonaceous residue is allowed after acid digestion, but quantitative filtration, washing, and merging of the filtrates should be used to ensure quantitative transfer of copper. The test object is the final copper-coated powder metallurgy oil-impregnated bearing. The sample is first extracted with petroleum ether in a Soxhlet extractor for 8 hours to remove the lubricating oil from the pores, then dried in a 100℃ drying oven for 120 minutes. After cooling, it is ground until all the sample passes through a 180μm standard sieve and mixed evenly.

[0095] Weigh approximately 0.500 g of the above powder sample into three portions and place them separately in polytetrafluoroethylene (PTFE) digestion vessels. Add 8 mL of hydrochloric acid and 2 mL of nitric acid, and digest under sealed conditions at 150 °C for 30 min. After cooling, if insoluble graphite or carbonaceous residues are present, filter quantitatively through a 0.45 μm PTFE membrane, and wash the residues several times with a small amount of dilute hydrochloric acid and deionized water. Combine the filtrate and washings and transfer them to a 100 mL volumetric flask. Dilute to the mark with deionized water and shake well to obtain the sample solution. Simultaneously prepare a blank digestion solution without the sample. The emission intensity of copper in the sample solution was determined using inductively coupled plasma atomic emission spectrometry (ICP-AES). The wavelength of the copper analytical line was 324.75 nm. A linear calibration curve was first established using a copper standard solution with a concentration range of 0–50 mg / L. The matrix of the calibration solution was consistent with that of the sample solution. The linear correlation coefficient of the calibration curve needed to be greater than 0.999. The sample solution was diluted to bring the copper concentration within the linear range of the calibration curve, and the total dilution factor f was recorded. In the calculation, the copper concentration read by the instrument was multiplied by f to convert it to the original concentration of 100 mL of the final volume solution, and then substituted into the formula as Cs. The total copper content was determined according to the following formula: General calculation formula:

[0096] In the formula, w(Cu) is the mass fraction of copper in the bearing, expressed as a percentage; Cs is the mass concentration of copper in the original diluted sample solution after conversion by the total dilution factor, in mg / L; Cb is the mass concentration of copper in the blank digestion solution, in mg / L; V is the volume of the sample solution after dilution, in mL; and ms is the mass of the powder sample weighed, in g. The relative deviation of the measured values ​​of the three parallel samples should be less than 1%, and the result is expressed as the arithmetic mean of the measured values ​​of the three parallel samples, and finally given as a mass fraction.

[0097] 5. Determination of steady-state friction coefficient: This test is used to evaluate the friction coefficient and stability of oil-impregnated bearings under radial load and without external lubrication, characterizing the bearing's self-lubricating performance and tribological properties. The test object is the final product, a copper-clad powder metallurgy oil-impregnated bearing, and three samples prepared under the same operating conditions are used. Since there is currently no specific test standard for chemically deposited copper-clad iron-based powder metallurgy oil-impregnated bearings under radial friction conditions, the industry-standard radial sliding friction and wear test method is adopted. This method is suitable for evaluating the friction pairs of sliding bearings with concentric inner and outer cylindrical surfaces. The sample is a ring bearing with an outer diameter of 16.0 mm and an inner diameter of 8.0 mm, forming a radial sliding friction pair with a hardened bearing steel shaft, with geometric relationships consistent with the applicable conditions.

[0098] The test was conducted on a vertical radial friction and wear testing machine. The grinding shaft was made of GCr15 bearing steel as specified in GB / T18254, and the working surface was ground to a surface arithmetic mean deviation Ra of 0.20μm±0.05μm. The diameter of the grinding shaft was selected according to the measured inner diameter of each specimen, so that the diameter clearance between the bearing inner hole and the grinding shaft was controlled at 0.015~0.025mm to avoid interference with the friction results due to zero clearance or interference. The shaft was mounted on the upper spindle and coaxially fitted with the inner hole of the specimen; the specimen was mounted in the lower bearing housing, which could swing around the horizontal axis. The ambient temperature was 23℃±2℃, and the relative humidity was 50%±10%. A radial normal load of 20N was applied, and the spindle speed was 230r / min. No external lubricant was added during the test, and the test was conducted continuously for 120min. The torque sensor continuously recorded the friction torque at a sampling interval of 0.1s, and the arithmetic mean of all friction torque values ​​recorded in the last 20min was taken as the steady-state average friction torque M. The steady-state friction coefficient is determined by the following formula: General calculation formula:

[0099] In the formula, μ is the steady-state friction coefficient; M is the steady-state average friction torque in N·mm; F ​​is the applied radial normal load in N; and r is the measured radius of the grinding shaft used for the corresponding sample in mm. The result is expressed as the arithmetic mean of the steady-state friction coefficients of the three samples, and the fluctuation range of the friction torque of each sample is recorded. After the test, the inner diameter of the sample is measured with an inside micrometer and the change in inner diameter is calculated to characterize the wear degree of the inner friction surface in mm.

[0100] Performance test data Table 1

[0101] As shown in Table 1, the test results of each embodiment exhibit a well-matched overall performance in terms of five indicators: open porosity, volumetric oil content, radial crushing strength, total copper content, and steady-state friction coefficient. Examples 1 and 3 demonstrate the most outstanding overall performance, achieving high radial crushing strength and low steady-state friction coefficient while maintaining high open porosity and volumetric oil content. This indicates that within a given formulation range and process window, the matching between pressing density, sintering regime, and copper deposition amount can simultaneously consider oil-containing space, load-bearing capacity, and tribological properties. In Example 2, due to lower pressing pressure and decreased compact density, porosity and oil content increased accordingly, but radial crushing strength decreased significantly, reflecting the trade-off between matrix density and load-bearing capacity and oil storage space. Examples 4 and 5 show that even with moderate variations in formulation dosage and copper deposition amount, all indicators remain within a coordinated range, verifying the process tolerance of the scheme.

[0102] Comparative Examples 1 and 2, with pressing pressure as the single variable, were located on opposite sides of a predetermined pressure range. Their open porosity and radial crushing strength exhibited opposite changes. Insufficient pressure resulted in excessively high porosity and deteriorated strength and frictional properties, while excessive pressure increased strength but significantly reduced the oil-containing space and increased the friction coefficient. Both of these factors confirm the necessity of the pressing pressure range. Comparative Example 3 reduced the amount of copper-tin pre-alloy powder to outside the formula range, resulting in a decrease in total copper content and radial crushing strength, while increasing the steady-state friction coefficient. Comparative Example 4 showed a significant decrease in strength after excessive introduction of flake graphite powder. Comparative Example 5 showed a simultaneous deterioration in radial crushing strength and steady-state friction coefficient after reducing the amount of manganese sulfide powder. Comparative Example 6 used a relatively low degreasing temperature, resulting in insufficient removal of the forming lubricant and the formation of a small amount of carbon residue in the subsequent high-temperature stage, adversely affecting sintering bonding and surface activation. Comparative Example 7 used an excessively high sintering temperature, leading to significant pore shrinkage and localized melting. Although copper deposition still occurred on the outer surface, the net weight gain was significantly lower than in the examples. Comparative Examples 8 to 10 varied the recovery time at atmospheric pressure, the absolute vacuum pressure, and the pH of the plating solution. Comparative Example 9 exhibited significant boiling at 60°C and 15 kPa, leading to instability in the deposition process. Comparative Example 10, while maintaining a relatively clear plating solution at pH 12.0, showed a decreased glyoxylic acid reduction rate and a prolonged deposition induction period, indicating that both vacuum pulse parameters and alkalinity affect the copper deposition rate and stability. Comparative Examples 11, 13, and 14 employed palladium-activated atmospheric pressure immersion plating, water vapor-displaced atmospheric pressure immersion plating, and single vacuum immersion followed by atmospheric pressure immersion plating, respectively. The increase in total copper content and mass was less significant than in the examples, suggesting insufficient renewal of the plating solution in the deep pores without repeated vacuum pulses. Comparative Example 12, without refining, activation, or chemical copper deposition, underwent direct vacuum oil immersion, resulting in the highest steady-state friction coefficient among all samples.

[0103] Comparative Examples 1-10 primarily employed single-factor boundary crossings or changes in a single process parameter to examine the impact of each parameter. Comparative Examples 11-14 represented overall comparisons of different process paths, simultaneously altering activation methods, pressure processes, or deposition methods; therefore, they are not presented as strictly single-variable experiments. In each example, copper-tin pre-alloy powder, flake graphite powder, manganese sulfide powder, and copper deposition layers coexisted. However, existing controls did not establish complete factorial combinations; therefore, the data in Table 1 are used to demonstrate the trends in the influence of each formulation and process condition on strength, oil content, and tribological properties, rather than to assert synergistic effects between components exceeding the sum of their individual contributions. Overall, under conditions of adding copper source, glyoxylic acid, and alkalinity according to the actual deposition amount and with a copper source utilization rate of approximately 80%, each example still achieved high radial crush strength and low steady-state friction coefficient while maintaining the oil content space. Vacuum pulsed chemical copper deposition, compared to atmospheric pressure immersion plating and single vacuum immersion, exhibited better overall performance in terms of copper coverage on the inner wall of the pores and tribological properties.

[0104] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A copper-clad powder metallurgy oil-impregnated bearing, characterized in that, The bearing comprises a sintered metal matrix and connecting channels distributed within the sintered metal matrix. The sintered metal matrix is ​​obtained by pressing, degreasing, sintering, and finishing a mixed powder. The mixed powder comprises reduced iron powder, copper-tin pre-alloy powder, graphite powder, and manganese sulfide powder. Based on 100 parts by weight of reduced iron powder, the copper-tin pre-alloy powder comprises 5.0–8.0 parts by weight, the graphite powder comprises 1.0–1.6 parts by weight, and the manganese sulfide powder comprises 0.4–0.8 parts by weight. The total copper content of the bearing is 5.5–9.8 wt%, the porosity of the bearing is 14–22%, and the inner surface of the connecting channels and the outer surface of the sintered metal matrix both have a copper deposition layer. The copper deposition layer is formed by a vacuum pulsed chemical copper deposition process in a chemical copper plating solution, and its mass is 1.5–3.5% of the mass of the sintered metal matrix.

2. The copper-clad powder metallurgy oil-impregnated bearing according to claim 1, characterized in that, The reduced iron powder has a D50 particle size of 45–90 μm, the copper-tin pre-alloyed powder has a D50 particle size of 20–45 μm, the graphite powder has a D50 particle size of 10–30 μm, and the manganese sulfide powder has a D50 particle size of 5–25 μm.

3. The copper-clad powder metallurgy oil-impregnated bearing according to claim 2, characterized in that, The copper-tin pre-alloyed powder is composed of 88-92 wt% copper and 8-12 wt% tin, the reduced iron powder has a median particle size of 45-60 μm, the graphite powder is flake graphite, and the manganese sulfide powder is in powder form.

4. A method for preparing a copper-clad powder metallurgy oil-impregnated bearing as described in any one of claims 1 to 3, characterized in that, Includes the following steps: S1: Mix reduced iron powder, copper-tin pre-alloyed powder, graphite powder and manganese sulfide powder evenly according to the proportions described in any one of claims 1 to 3 to obtain a mixed powder; S2: The mixed powder is loaded into a bearing molding die and pressed into an annular preform under a pressure of 400–550 MPa, controlling the apparent density of the annular preform to be 5.9–6.3 g / cm³. 3 ; S3: The annular compact is heated to 380-450°C in a nitrogen atmosphere and held for 30-60 minutes for degreasing. Then, it is heated to 860-910°C in a hydrogen protective atmosphere and held for 25-45 minutes for sintering. After being cooled to below 150°C in the furnace, it is taken out of the furnace to obtain an iron-based porous sintered compact. S4: The iron-based porous sintered billet is dimensionally refined, and the inner and outer diameters of the bearing are reserved for dimensional compensation based on the subsequent copper deposition amount, so that the copper-clad bearing billet after the reduction treatment in step S6 reaches the target finished product size; the refined sintered billet is sequentially degreased and cleaned, acid activated and copper deposition initiated to obtain an activated sintered billet; S5: The activated sintered blank is completely immersed in the electroless copper plating solution. The processing container holding the activated sintered blank and the electroless copper plating solution is alternately vacuumed and restored to normal pressure at 55-70°C. This allows the electroless copper plating solution to enter the connecting channels of the activated sintered blank and cause electroless copper deposition. The mass increase rate of the sintered blank is controlled to be 1.5-3.5%, and a copper-deposited sintered blank is obtained. S6: The copper deposited sintered blank is subjected to deionized water vacuum pulse cleaning, then dried, and then subjected to reduction treatment at 300-380℃ for 30-60 min in a hydrogen-containing protective atmosphere to obtain copper-clad bearing blank. S7: Place the copper-clad bearing blank in lubricating oil, evacuate it at 70-90°C to an absolute pressure not exceeding 10 kPa and maintain it for 15-30 minutes, then restore it to normal pressure and maintain it for 20-40 minutes. Remove it and remove the surface oil to obtain a copper-clad powder metallurgy oil-impregnated bearing.

5. The method for preparing a copper-clad powder metallurgy oil-impregnated bearing according to claim 4, characterized in that, In step S5, the electroless copper plating solution contains copper sulfate pentahydrate, disodium ethylenediaminetetraacetate dihydrate, glyoxylic acid (calculated as pure glyoxylic acid), polyethylene glycol with an average molecular weight of 400-800, and 2,2'-bipyridine, and sodium hydroxide is used to adjust the pH of the electroless copper plating solution to 12.2-12.

6.

6. The method for preparing a copper-clad powder metallurgy oil-impregnated bearing according to claim 4, characterized in that, In step S5, after the activated sintered blank is completely immersed in the chemical copper plating solution, the absolute pressure of the treatment container is reduced to 40-60 kPa and maintained for 2-5 min, then restored to atmospheric pressure and maintained for 3-8 min. The vacuuming and atmospheric pressure restoration operation is repeated 3-6 times, and then chemical deposition is continued at atmospheric pressure and 55-70°C for 15-35 min.

7. The method for preparing a copper-clad powder metallurgy oil-impregnated bearing according to claim 4, characterized in that, In step S4, acid activation is performed using a hydrochloric acid aqueous solution with a mass concentration of 1.0–2.5%, treated at 20–35°C for 30–90 seconds.

8. The method for preparing a copper-clad powder metallurgy oil-impregnated bearing according to claim 4, characterized in that, In step S4, the copper deposition initiation treatment involves immersing the acid-activated sintered blank in an initiation solution containing copper sulfate pentahydrate and sodium citrate with a pH of 4.5–5.5 for 15–60 seconds.

9. The method for preparing a copper-clad powder metallurgy oil-impregnated bearing according to claim 4, characterized in that, In step S6, the deionized water vacuum pulse cleaning is performed at least twice. Each cleaning includes reducing the absolute pressure to 8-20 kPa and maintaining it for 2-5 minutes before restoring it to normal pressure, until the pH of the final cleaning solution is 6.5-7.5 and the conductivity is not higher than 100 μS / cm. Drying is carried out at 80-120℃ and an absolute pressure not higher than 10 kPa, with a drying time of 60-120 minutes.

10. The method for preparing a copper-clad powder metallurgy oil-impregnated bearing according to claim 4, characterized in that, In step S7, the polyalphaolefin base oil of the lubricating oil used has a kinematic viscosity of 28–68 mm at 40°C. 2 / s.